The Influence of Wedding Photography as Visual Communication in the Promotion of Batak and Minang Traditional Culture: A Case Study in @fng _photography - Ruly Dwi Arista (Journal of Information Technology, computer science and Electrical Engineering, 2024)
Technological advances continue to evolve over time, including in the world of photography. Photography itself is a process or method to create an image or photo of an object by recording the reflection of light falling on the object in a light-sensitive medium. One branch of photography is Wedding photography, which is taken during the couple's wedding. With the development of the times, marriages that used to always follow local customs are now becoming more and more rare. Using traditional clothes in weddings is one of the efforts to preserve Indonesian culture. One of the tribes that still often wear traditional clothes in weddings is the Batak and Minang customs.The author obtained photography documentation of Batak and Minang traditional weddings from the photo studio fng photography Studio, It is a photo studio that consistently documents Batak and Minang traditional weddings. The photos uploaded by the account introduce the culture through the display of traditional Batak and Minang traditional clothing, which is usually worn on special moments such as wedding ceremonies. Uploads on @fng_photography Instagram account are a form of visual communication that also serves as a cultural promotion. These photos allow Instagram users around the world to see and appreciate the uniqueness of the Batak and Minang cultures, so it is hoped that they will add to their insight into the rich culture found in Indonesia.